Improvement of Bone Health and Initiation of Puberty Development in Camurati-Engelmann Disease With Glucocorticoid and Losartan Treatment: A Case Report and Review of Literature - Cui, Lijia; Li, Qian; Guan, Wenmin; Yu, Wei; Li, Xiang; Xia, Weibo; Jiang, Yan (Frontiers in Endocrinology, 2022)
Camurati-Engelmann Disease (CED) is a rare sclerosing bone disease, sometimes associated with delayed puberty. The treatment effect of glucocorticoid and angiotensin II receptor blocker (ARB) in bone health and puberty development remain unclear. We report a case of an 18-year-old girl presented for a history of enlarged head, pain of lower limbs, and no menstrual onset or breast development. Radiographs revealed thickening of skull and cortices in the diaphysis, but sparse bone trabeculae in the spine and metaphysis. Sanger sequencing detected a mutation of c. 652C>T (p. R218C) in the gene TGFB1, and confirmed the diagnosis of CED. After treatment of medium to small dosage of prednisone and losartan for 28 months, we observed improvement of bone mass in spine and hip and body fat mass, and surprisingly found initiation of puberty development. By a systemic review of current treatment strategies in CED patients, we found most cases reported relief of bone pain after treatment of glucocorticoid or ARB, but none haven’t reported the outcome of hypogonadotropic hypogonadism. We propose that, long-term use of glucocorticoid combined with ARB, may inhibit the activation of TGFβ1 in CED, improve adipogenesis, and thus initiate puberty development, and improve the bone mass in spine and hip.